Lulusan Institut Teknologi Kalimantan Sebelum dan Sesudah Pandemi Covid-19 - Diana Nurlaily; Ridhwan Haliq; Chaerul Qalbi A.M; Andi Idhil Ismail; Gad Gunawan; Devy Setiorini Sa’adiyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Every year, a program called a "tracer study" is run to collect and analyze data from graduates (a year after graduation). Seeks to guarantee that graduates have good work and submit it on time following university or institute criteria after graduation. Within 1-2 months of filling it out, a data analyst processes the data and validates its accuracy. Data for 10 study programs were collected, and comparisons were made between the graduation years of 2019 and 2020. In 2020, the Covid-19 pandemic started. The Institut Teknologi kalimantan (ITK) was significantly impacted by Covid-19, which led to all work being done online on campus. Evaluation criteria for ITK include the length of time it takes graduates to find employment, their GPA, the nature of their alumni employment, and their reasons for not finding employment one year after graduation. In order to be able to create more qualified alumni, the rate ranking approach will help examine the success of the study program and provide an evaluation of the study program. This paper's two lowest-ranking disciplines are electrical engineering, materials engineering, and metallurgy..